1919
DOI: 10.1001/jama.1919.02610060004002
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Associated With Malignant Neoplasia

Abstract: symptoms suggestive of coronary thrombosis, the elec¬ trocardiograms were compared with those in dogs.Results.-The results may be thus summarized :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1934
1934
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…29 In the head and neck region, TB can coexist with carcinoma of the larynx, 6 tonsil and nasopharynx. 30 However, the strongest association is with carcinoma of the larynx and the pharynx.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In the head and neck region, TB can coexist with carcinoma of the larynx, 6 tonsil and nasopharynx. 30 However, the strongest association is with carcinoma of the larynx and the pharynx.…”
Section: Treatmentmentioning
confidence: 99%
“…Coexistence with cancer and HIV Tuberculosis can coexist with cancer in different organs, in the same organ, or even in the same microscopic slide. 29 In the head and neck region, TB can coexist with carcinoma of the larynx, 6 tonsil and nasopharynx. 30 However, the strongest association is with carcinoma of the larynx and the pharynx.…”
Section: Treatmentmentioning
confidence: 99%
“…Discussion of the relationship between lung cancer and TB has emphasized the pathogenicity. [13][14][15] A significantly higher incidence of lung cancer in patients with previous TB has been documented in cigarette smoking patients, 16 and some studies have suggested the coexistence of lung cancer and TB is coincidental. 17 However, recent Asian epidemiological studies have shown that TB is associated with a higher risk of lung cancer, independent of smoking.…”
Section: Discussionmentioning
confidence: 99%